Given the equation below, solve for the general solutions.
w = dependent variable, v = independent variable
1. w (4v + w) dv - 2 (v^2 - w) dw = 0
"M_w=4v+2w\\neq N_v=-4v"
so the equation is not exact.
"w(v)=\\displaystyle{\\sum_{n=0}^{\\infin}}a_nv^n"
"w'(v)=\\displaystyle{\\sum_{n=1}^{\\infin}}na_nv^{n-1}"
"4v\\displaystyle{\\sum_{n=0}^{\\infin}}a_nv^n+(\\displaystyle{\\sum_{n=0}^{\\infin}}a_nv^n)^2-2v^2+2\\displaystyle{\\sum_{n=0}^{\\infin}}a_nv^n\\cdot \\displaystyle{\\sum_{n=1}^{\\infin}}na_nv^{n-1}=0"
"4a_1v^2+(2a_0a_2+a_1^2)v^2+(6a_0a_3+4a_1a_2+2a_2a_1)v^2=2v^2"
"4a_1+2a_0a_2+a_1^2+6a_0a_3+6a_1a_2=2"
"a_0=0"
Then:
"a_2=\\frac{2-4a_1-a_1^2}{6a_1}"
"y(x)=a_1x+\\frac{2-4a_1-a_1^2}{6a_1}x^2"
Comments
Leave a comment